IMPLEMENTASI KEBIJAKAN PERATURAN PEMERINTAH NOMOR 11 TAHUN 2021 TENTANG PENGELOLAAN BADAN USAHA MILIK DESA (Studi di Desa Karang Dima Kecamatan Labuhan Badas) - Wulan Nurrohmah; Dedi Supriadi (Jurnal Ekonomi & Bisnis, 2026)
This research aims to examine and analyze the implementation of Government Regulation Number 11 of 2021 on Village-Owned Enterprise (BUMDes) Management and the inhibiting factors in Karang Dima Village, Labuhan Badas District. BUMDes Benta Makmur was selected as the research object due to its relatively optimal performance with a community benefit level of 78, the highest among seven villages in Labuhan Badas. This study uses a descriptive qualitative methodology. Data were obtained through in-depth interviews with BUMDes management, village government officials, Village Consultative Body (BPD) members, village facilitators, and community members, supported by observation and documentation. Data analysis uses Edward III's policy implementation theory encompassing four variables: communication, resources, disposition, and bureaucratic structure. Inhibiting factors were analyzed using Bambang Sunggono's theory covering policy content, information, support, and potential distribution. The results indicate that implementation of PP No. 11/2021 has progressed with participatory communication through village deliberations, increased fund allocation from IDR 6 million in 2014 to IDR 300 million in 2025, and strengthened BUMDes organizational structure. However, obstacles exist including general policy content, limited technical information, weak community support, and mismatch between task distribution and management capacity. This research recommends continuous human resource capacity building, standard guidelines for duties and functions, strengthened socialization, and improved community participation.